Offshore Freshened Groundwater in Continental Margins. (4th January 2021) - Micallef, Aaron; Person, Mark; Berndt, Christian; Bertoni, Claudia; Cohen, Denis; Dugan, Brandon; Evans, Rob; Haroon, Amir; Hensen, Christian; Jegen, Marion; Key, Kerry; Kooi, Henk; et al.
Abstract: First reported in the 1960s, offshore freshened groundwater (OFG) has now been documented in most continental margins around the world. In this review we compile a database documenting OFG occurrences and analyze it to establish the general characteristics and controlling factors. We also assess methods used to map and characterize OFG, identify major knowledge gaps, and propose strategies to address them. OFG has a global volume of 1 × 10 6 km 3 ; it predominantly occurs within 55 km of the coast and down to a water depth of 100 m. OFG is mainly hosted within siliciclastic aquifers on passive margins and recharged by meteoric water during Pleistocene sea level lowstands. Key factors influencing OFG distribution are topography‐driven flow, salinization via haline convection, permeability contrasts, and the continuity/connectivity of permeable and confining strata. Geochemical and stable isotope measurements of pore waters from boreholes have provided insights into OFG emplacement mechanisms, while recent advances in seismic reflection profiling, electromagnetic surveying, and numerical models have improved our understanding of OFG geometry and controls. Key knowledge gaps, such as the extent and function of OFG, and the timing of their emplacement, can be addressed by the application of isotopic age tracers, joint inversion of electromagnetic and seismic reflection data, and development of three‐dimensional hydrological models. We show that such advances, combined with site‐specific modeling, are necessary to assess the potential use of OFG as an unconventional source of water and its role in sub‐seafloor geomicrobiology. Plain Language Summary: This review paper considers offshore freshened groundwater (OFG), which is water hosted in sediments and rocks below the seafloor, with a total dissolved solid concentration lower than seawater. We have compiled >300 records to demonstrate that freshened groundwater occurs offshore on most continents around the world and has a global volume of 1 × 10 6 km 3 . The majority of OFG was deposited when sea level was lower than today and is hosted in sandy sub‐seafloor layers that are located within 55 km of coasts in water depths less than 100 m. We present a range of geochemical, geophysical, and modeling approaches that have successfully been used to investigate OFG systems. We also propose approaches to address key scientific questions related to OFG, including whether it may be used as an unconventional source of potable water in coastal areas. Key Points: Most known OFG is located at water depths of <100 m within 55 km of the coast, hosted in siliciclastic aquifers in passive margins Key gaps in knowledge include the extent and function of OFG systems, as well as the mechanism and timing of emplacement Isotopic tracers, jointly inverted geophysical data and 3‐D hydrological models can help address these knowledge gaps